Chitosan, Polyethylene Glycol and Polyvinyl Alcohol Modified MgFe2O4 Ferrite Magnetic Nanoparticles in Doxorubicin Delivery: A Comparative Study In Vitro - Deevak Ramnandan; Seipati Mokhosi; Aliscia Daniels; Moganavelli Singh (Molecules, 2021)
Cancer-based magnetic theranostics has gained significant interest in recent years and can contribute as an influential archetype in the effective treatment of cancer. Owing to their excellent biocompatibility, minute sizes and reactive functional surface groups, magnetic nanoparticles (MNPs) are being explored as potential drug delivery systems. In this study, MgFe2O4 ferrite MNPs were evaluated for their potential to augment the delivery of the anticancer drug doxorubicin (DOX). These MNPs were successfully synthesized by the glycol-thermal method and functionalized with the polymers; chitosan (CHI), polyvinyl alcohol (PVA) and polyethylene glycol (PEG), respectively, as confirmed by Fourier transform infrared (FTIR) spectroscopy. X-ray diffraction (XRD) confirmed the formation of the single-phase cubic spinel structures while vibrating sample magnetometer (VSM) analysis confirmed the superparamagnetic properties of all MNPs. Transmission electron microscopy (TEM) and nanoparticle tracking analysis (NTA) revealed small, compact structures with good colloidal stability. CHI-MNPs had the highest DOX encapsulation (84.28%), with the PVA-MNPs recording the lowest encapsulation efficiency (59.49%). The 3-(4,5-dimethylthiazol-2-yl)-2,5 diphenyl tetrazolium bromide (MTT) cytotoxicity assays conducted in the human embryonic kidney (HEK293), colorectal adenocarcinoma (Caco-2), and breast adenocarcinoma (SKBR-3) cell lines showed that all the drug-free polymerized MNPs promoted cell survival, while the DOX loaded MNPs significantly reduced cell viability in a dose-dependent manner. The DOX-CHI-MNPs possessed superior anticancer activity (<40% cell viability), with approximately 85.86% of the drug released after 72 h in a pH-responsive manner. These MNPs have shown good potential in enhancing drug delivery, thus warranting further optimizations and investigations.